Description of malocclusion based on Dewey modified angle ‎classification in mentally disabled on special need education in ‎Jember district, Indonesia - Budirahardjo, Roedy; Setyorini, Dyah; Julia, Heni; Sulistiyani; Hadnyanawati , Hestieyonini; Probosari , Niken; Sukanto (International Journal of Dental Research, 2025)
Introduction: Malocclusion is a condition of disharmony between the teeth, jaw bones, skull bones and muscles which is often found in ‎mentally retarded children. Limitations in taking care of themselves and the absence of early and routine socialization to maintain oral health ‎are causes of malocclusion in children. mentally disabled.‎Objective: This study aims to identify features of malocclusion based on the modified Dewey Angle classification in mentally re-tarded ‎children in special schools in Jember Regency, East Java, Indonesia. ‎Method: This quantitative descriptive research involved 105 mentally retarded students from five special schools in Jember Regency who ‎were selected proportionally. Data collection was carried out through intraoral examination using basic dental instruments to assess the ‎relationship between the upper and lower first molars. ‎Results: The results showed that the prevalence of Angle malocclusion was 72.4% with the highest classification being Angle class I at ‎‎59.0%, followed by class III at 8.6% and class II at 4.8%. Dewey modification for class I shows type 1 as the dominant type (17.1%) in ‎frequency multiple highest in combined type 1 and type 2 (13.3%). ‎Conclusion: The results of this study provide an important contribution in identifying and treating dental health problems in chil-dren with ‎intellectual disabilities, and provide a basis for developing oral health care and education strategies‎.